Diversity and Function of Phage Encoded Depolymerases - Knecht, Leandra E.; Veljkovic, Marjan; Fieseler, Lars (Frontiers in Microbiology, 2020)
Bacteriophages of the Podoviridae family often exhibit depolymerases, e.g. lyases and hydrolases, as structural components of the virion. The enzymes are connected to the baseplate and appear as tail spike or tail fiber proteins, respectively. After specific binding to capsular polysaccharides (CPS), exopolysaccharides (EPS) or lipopolysaccharide (LPS) of the host bacteria, polysaccharide-repeating units are specifically cleaved by the enzymes. Finally, the phage reaches the last barrier, e.g. the cell wall, injects its DNA, and infects the cell. Recently members of the other bacteriophage families, e.g. in the Ackermannviridae, Myoviridae, and Siphoviridae families producing similar enzymes have also been described. In this mini-review the diversity, structure, and function of phage encoded CPS-, EPS- and LPS-degrading lyases and hydrolases are summarized. The function of the enzymes is described in terms of substrate specificity and applications in biotechnology.